Betty Ford : candor and courage in the White House - Greene, John Robert, 1955- (Modern first ladies., 2004)
""Greene's engaging biography gives Betty Ford her rightful place in history-as an outspoken first lady whose public positions did not always conform to her husband's and as a courageous advocate for solutions to breast cancer and substance abuse.""--Susan Hartmann, author of From Margin to Mainstream: American Women and Politics since 1960 ""Betty Ford was like no other First Lady before or since, and John Robert Greene shows why.""-Herbert Parmet, author of Presidential Power from the New Deal to the New Right ""A fitting tribute to a free spirit and most indomitable First Lady.""-James Canno